Tenets of Mah Meri oral tradition and community development goals in Pulau Carey, Selangor, Malaysia - Zuhairi, Mohd Haikal (2023)
The are many types of Malaysia Indigenous people that are also known as Orang Asli for Malaysia Peninsular which consists of eighteen different ethnicities, and the Mah Meri people are one of them, under the big Senoi group. Almost all of the Mah Meri people live along the coastal region of the west part of Selangor, from Sungai Pelek up to Pulau Carey. For many years, the government and many other stakeholders have done initiatives to improve the Orang Asli, however, the results were not satisfactory. Despite the efforts taken, the Orang Asli is still considered the least-developed community compared to the other mainstream people. The executed development initiatives and policies may be more quantity-oriented, instead of quality-oriented. The Orang Asli might have different values and belief systems which can vary. Thus, ‘one shoe fits all’ approaches might not be effective to be applied to the Orang Asli, but better carefully-designed approaches may fit better with the people’s needs and values. This study attempted to investigate tenets of the Mah Meri oral tradition, to understand community development goals from the perspective of the Mah Meri people, and to discuss the influences of the tenets in Mah Meri's perspectives towards their community development goals. By using the theory of Structural Functionalism this research analyses the tenets of the Mah Meri oral tradition to understand their meanings and influences, besides their roles in achieving Mah Meri community development goals. In-depth interviews were conducted among the Mah Meri respondents, covering the area of oral traditions and contemporary issues, to synthesis the relationship between the oral tradition tenets with their community development goals. Five identified tenets are revolved around the Mah Meri’s oral tradition which are Kemali, Tulah, Bentan, Maruk, and Tuil. It is found that most of the tenets are bad karmic-consequence oriented, that instils fear, instead of reward-oriented that instils motivation. The findings show that the essences of these five tenets are universal, and are still believed by the Mah Meri people. However, they are manifested in different views, forms and practices, as the contemporary context of economics, social and politic development are different compared to the past. The values and belief system of the Mah Meri people are still been believed and practised, even in different forms and contexts today. The Mah Meri community development goals are still sustained, aimed and favoured by the Mah Meri today as well, being shaped and influenced by the tenets of the Mah Meri oral tradition. Thus, this research is important to understand how the Mah Meri people behave and react to their livelihood, besides perceiving their community development goals which are affected and influenced by the tenets of their oral tradition.